1956
DOI: 10.1126/science.124.3212.103
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Free Neutrino: a Confirmation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
428
1
4

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(458 citation statements)
references
References 5 publications
6
428
1
4
Order By: Relevance
“…In 1937, neutrinos were themselves hypothetical, and their properties unknown. The experimental study of neutrinos commenced with their discovery [13] in 1956, but their observed properties seemed to disfavor Majorana's idea. Specifically, there seemed to be a strict distinction between neutrinos and antineutrinos.…”
Section: Analysis Of Majorana Neutrinosmentioning
confidence: 99%
“…In 1937, neutrinos were themselves hypothetical, and their properties unknown. The experimental study of neutrinos commenced with their discovery [13] in 1956, but their observed properties seemed to disfavor Majorana's idea. Specifically, there seemed to be a strict distinction between neutrinos and antineutrinos.…”
Section: Analysis Of Majorana Neutrinosmentioning
confidence: 99%
“…This opened the door to the use of neutrinos as a sensitive probe of particle physics. This pioneering experiment used the delayed coincidence technique to search for the reaction anti-ν e + p → e + + n where an electron antineutrino interacted with a free proton in a large tank filled with cadmium loaded liquid scintillator [1,2].…”
Section: Fact and Mysteries In Neutrino Physicsmentioning
confidence: 99%
“…The Monte Carlo sample contains all dilepton final states, including τ 's, with inclusive τ lepton decay. Tau leptons are decayed using TAUOLA [8]. These high p T events (hard scattered) are passed through a detailed detector silumation based on GEANT 3 [9].…”
Section: Signal and Backgroundmentioning
confidence: 99%